The effect of maternal scaffolding on problem solving skills during early childhood - Ismail, Nellie; Ismail, Khaidzir; Mohamad Aun, Nur Saadah (SAGE Publications, 2019)
During early childhood years, children’s ability to solve complex and challenging problems is still limited.Therefore, they still need help and support from parents. The objective of this study was to examine the effect of maternal scaffolding on problem solving skills during early childhood. Participants (40 mother-child dyads)were randomly assigned tofour experimental groups thatapplied variousscaffolding techniques,either contingent, verbal, swing or demonstration. The data was analyzed using split-plot analysisof variance(SPANOVA). There were significant differencesin the mean scores of problem solving skills at pre-posttest[F= (2, 35) = 3.84, p≤ 0.05]. Children’s problem solving skills increased across the three testing times.Moreover, there wereno significant interaction between time (pre-posttest) and groups[(F= 6, 72) = 0.78, p> 0.05]. There were also no significant differences in the mean scores of problem solving skills among thefour groups[F(3, 36) = 0.56, p> 0.05)].Findings imply that children can internalize the learning processes during the scaffolding sessionover a longer period. Therefore, it is important for parents to give an appropriate support based on the children’s ability in helping them to increase their problem solving skills.